Paneth Cell Dysfunction Mediates Alcohol‐related Steatohepatitis Through Promoting Bacterial Translocation in Mice: Role of Zinc Deficiency. Issue 5 (10th March 2020) - Zhong, Wei; Wei, Xiaoyuan; Hao, Liuyi; Lin, Tai‐Du; Yue, Ruichao; Sun, Xinguo; Guo, Wei; Dong, Haibo; Li, Tianjiao; Ahmadi, Ali R.; Sun, Zhaoli; Zhang, Qibin; et al.
Abstract : Background and Aims: Microbial dysbiosis is associated with alcohol‐related hepatitis (AH), with the mechanisms yet to be elucidated. The present study aimed to determine the effects of alcohol and zinc deficiency on Paneth cell (PC) antimicrobial peptides, α‐defensins, and to define the link between PC dysfunction and AH. Approach and Results: Translocation of pathogen‐associated molecular patterns (PAMPs) was determined in patients with severe AH and in a mouse model of alcoholic steatohepatitis. Microbial composition and PC function were examined in mice. The link between α‐defensin dysfunction and AH was investigated in α‐defensin‐deficient mice. Synthetic human α‐defensin 5 (HD5) was orally given to alcohol‐fed mice to test the therapeutic potential. The role of zinc deficiency in α‐defensin was evaluated in acute and chronic mouse models of zinc deprivation. Hepatic inflammation was associated with PAMP translocation and lipocalin‐2 (LCN2) and chemokine (C‐X‐C motif) ligand 1 (CXCL1) elevation in patients with AH. Antibiotic treatment, lipopolysaccharide injection to mice, and in vitro experiments showed that PAMPs, but not alcohol, directly induced LCN2 and CXCL1. Chronic alcohol feeding caused systemic dysbiosis and PC α‐defensin reduction in mice. Knockout of functional α‐defensins synergistically affected alcohol‐perturbed bacterial composition and the gut barrier and exaggerated PAMP translocation and liver damage. Administration of HD5 effectively altered cecal microbial composition, especially increased Akkermansia muciniphila, and reversed the alcohol‐induced deleterious effects. Zinc‐regulated PC homeostasis and α‐defensins function at multiple levels, and dietary zinc deficiency exaggerated the deleterious effect of alcohol on PC bactericidal activity. Conclusions: Taken together, the study suggests that alcohol‐induced PC α‐defensin dysfunction is mediated by zinc deficiency and involved in the pathogenesis of AH. HD5 administration may represent a promising therapeutic approach for treating AH.